Peran Teknologi dalam Mendukung Pembelajaran Merdeka Belajar - Sitti Hajar; Andi Marwan (Publikasi dan UKI Toraja Press Universitas Kristen Indonesia Toraja, 2024)
Education is the main foundation in forming a competent, adaptive and competitive young generation in the ever-growing digital era. In the effort towards the vision of the Independent Curriculum, educational technology plays an important role in revolutionizing the learning and teaching process. This not only provides wider access to educational resources, but also allows for a more dynamic and tailored learning approach to individual needs. This research stage was carried out to find out the role of technology in supporting independent learning. This type of research is qualitative research using library research. The data collection technique in this research is by identifying articles, journals and other sources related to the problem. The aim of this research is the role of technology in supporting independent learning. Efforts to improve the quality of education in Indonesia must be accompanied by technological developments. Technology in education is a forum for facilitating the learning process so that it can be used as a learning resource to create efficient and effective education